Incentives matter sometimes: On the differences between league and Cup football matches - Jan C. van Ours; Martin A. van Tuijl (Tinbergen Institute, 2024)
Economic agents react to incentives, and this holds true for professional football teams as well. Double round-robin and single-match elimination represent two opposite competition regimes, with incentives varying distinctly between them. At the level of individual matches, a single defeat needs not be fatal under a double round-robin regime, unlike in a single-match elimination system. Utilizing data from Dutch professional football spanning from the 2004/05 season to the 2022/23 season, we compare single-match elimination Cup matches with double round-robin league matches, focusing on stadium attendance, match results, and home advantage. Stadium attendance tends to be lower in Cup matches, although the gap narrows in later stages of the Cup tournament, and it eventually disappears. The home advantage is similar in Cup matches and league matches, but when Cup matches extend beyond regular time, the home advantage diminishes. In later stages of the Cup tournament, both during extra time and penalty shootouts, home advantage appears to be virtually absent.
Keywords: L83; 330; Football incentives; stadium attendance; home advantage